"My greatest challenge happens to be my greatest success": Overcoming barriers during an early preservice teacher practicum with a high percentage of dual language learners. (September 2019) - Durham, Sean; Harrison, Jamie; Barry, Nancy H
This qualitative study investigated preservice teachers' experiences working with dual language learners within an early university-based practicum with young children. Our data were multiple reflective journal entries that each preservice teacher composed during the practicum. Our initial analysis revealed a subset of preservice teachers who described major challenges in their initial work with dual language learners but ultimately formed more professional dispositions toward working with this population. A constructivist paradigm guided our further collaborative, iterative coding process that yielded three principal themes: (1) struggling to connect with dual language learners, (2) trying out "child-centered" approaches, and (3) articulating a sense of professional empowerment. Additional research is needed to support teacher educators in their mission to empower all early childhood teachers to work effectively with dual language learners.